Analysis on consumer behavior when purchasing cell phones - Alsidieg Musa, Omar (2012)
Cell phones have become an integral part of human daily life and personal communication across the globe and these devices get rapid development every year with more technologies and enhanced specifications. Nowadays it is rare to find a young man or women without a cell phone attached with him/her. Cell phone market is booming and every year there are new brands in the market and competition increasing rapidly with significant growth between the major manufactures of cell phones. Nowadays it becomes more difficult for new firms to access the cell phones market with very strong market barriers due to oligopolistic competition. Few cell phone manufacturers dominated the market and each oligopolist is likely to be aware of the actions of the others. It is very hard to compete in a market where Nokia, Apple and Samsung for instance, and making the decisions to influence such complicated market is not easy and require a strategic planning and also understanding the consumer behavior when buying these brands in order to enter the cell phone market. This study will analyze how a young consumer make a decision to buy a cell phone, and what factors affect consumer behavior. The research goes far beyond these facets of consumer behavior and encompasses all of the behaviors that consumers display in searching for, purchasing using, evaluating, and disposing of ew cell phone what is the key points that satisfy his/her needs. The pwpose ofthis study is to investigate the factors